PROSTATECTOM Y IN A GENERAL SURGICAL UNIT; CHANGING TRENDS - Sultan, Syed; Ahmed, Rashid; Khattak, Irfan -ud-Din; Quresh, Zaheer i; Ahmed, Ashfaq (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: This study compares the results of 104 consecutive transurethral and 61 consecutive open prostatectomies, performed in a General Surgical Unit in a District Hospital. The indication for surgery was acute retention in 65% of cases and prostatism in 35%. The mean post-operative stay was six and a half days for T.U.R. and fourteen and a half days for open prostatectomies.